The Encyclopaedia of Islam: Index - Edited by Bearman, P. J. [et al.] (Leiden, Neitherland E. J. Brill, 2009)
For more information about the Encyclopeadia of Islam Online visit www.brillonline.nl to view a free demo or to place your order.
Includes Illustrations
Keywords: Islamic Civilization